2018
DOI: 10.5301/ejo.5001011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of eyedrops containing cross-linked hyaluronic acid and coenzyme Q10 in treating patients with mild to moderate dry eye

Abstract: The XLHA + CoQ10 treatment showed greater effectiveness in DED compared to HA alone, probably due to the longer permanency on ocular surface and the antioxidant activity of CoQ10. Therefore, XLHA + CoQ10 eyedrops could represent a new possibility in dry eye treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
3
30
0
3
Order By: Relevance
“…There are few studies regarding cross-linked HA, especially in humans, 47,48 but these preliminary reports have confirmed that it could represent a new valid option for treatment of patients affected by mild-to-moderate dry eye.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies regarding cross-linked HA, especially in humans, 47,48 but these preliminary reports have confirmed that it could represent a new valid option for treatment of patients affected by mild-to-moderate dry eye.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recently, Postorino et al published their results about the use of cross-linked HA and coenzyme Q10 in treating patients with mild-to-moderate dry eye. 48 This was a randomized, single-masked, parallel group, and comparative study. Forty patients with mild-to-moderate dry eye disease were enrolled.…”
Section: Fig 2 Example Of a Crosslinked Ha Moleculementioning
confidence: 99%
“…In the first study conducted in vitro, [15] corneal epithelialization improved with two artificial tear formulations containing crosslinked hyaluronic acid combined with 0.02% and 0.4% urea; both compounds quantitatively improved the ocular surface. A recently published study examined the efficacy of an artificial tear containing crosslinked hyaluronic acid combined with coenzyme Q10 [16] and concluded that the resulting effect on the ocular surface is greater than that with hyaluronic acid alone. The hyaluronic acid/coenzyme Q10 combination led to a reduction in the OSDI score and in corneal and conjunctival staining.…”
Section: Contact Lenses and Mgdmentioning
confidence: 99%
“…Crosslinked hyaluronic acid confers a higher molecular weight to the polysaccharide chain and has been investigated in recent studies, used alone and combined with other elements. [15,16] The purpose of this study was to evaluate the clinical efficacy of 0.4% uncrosslinked hyaluronic acid and 0.2% galactoxyloglucan (tear A) and 0.15% crosslinked (CXL) hyaluronic acid, crocin, and liposomes (tear B) in dry eye disease caused by meibomian gland dysfunction.…”
mentioning
confidence: 99%
“…CoQ10 ist eine sehr wirksame Redoxkomponente der Elektronentransportkette in extramitochondrialen Membranen, in denen es antioxidativ und membranstabilisierend wirkt [28]. Es gibt Hinweise darauf, dass CoQ10 möglicherweise eine sinnvolle therapeutische Option für Augenerkrankungen wie das Glaukom [29,30], das "Trockene Auge" [31,32] Literatur…”
Section: Coenzym Q10unclassified